The effect of implantable cardioverter defibrillator in patients with cardiac resynchronizational therapy and diabetes mellitus. (19th May 2022) - Masszi, R; Merkel, E; Schwertner, W; Veres, B; Behon, A; Pinter, A; Osztheimer, I; Zima, E; Geller, L; Becker, D; Kosztin, A; Merkely, B
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): (NKFIA; NVKP_16-1-2016-0017 National Heart Program). Background: Heart failure (HF) and diabetes mellitus (DM) are common causes of death on their own, but the coexistance of these two diseases are especially fatal. 1 In DM, sudden cardiac death (SCD) is more common than in non-DM patients, however in many cases, implantable cardioverter defibrillator (ICD) could not prevent SCD. 2 Purpose: Our aim is to decide which device warrant higher life expectancy, cardiac resynchronizational therapy with or without defibrillator. Methods: We examined retrospectively 2525 CRT implanted patients, with a mean follow-up time of 4.6 years. Implantaions were based on the current guidelines. The primary endpoint was all-cause mortality, while our composite end-point were all-cause mortality and heart failure hospitalization. Results: In our population, 928 people (36%) had diabetes. We did not find statistical differences between age (68 vs. 68 years; p<0.099), gender (26% women, 23% women; p<0.08) LVEF (28% vs. 29% p<0.1425), incidence of atrial fibrillation (37% vs. 38%; p<0.76), implantation of an ICD (53% vs. 54%; p<0.847), NT-proBNP median levels (2939 pg/ml vs. 2778 pg/ml; p<0.35), and NYHA I (0, 5% vs. 0, 5%; p<0.898), and NYHA IV stadium (11% vs. 11%; p<0, 82). However DM patients had higher BMI (28 kg/m2 vs. 26 kg/m2; p<0.001), lower eGFR levels (57 ml/min/1, 73m2 vs. 60 ml/min/1, 73m2; p<0.011) higher prevalence of hypertonia (82% vs. 66%; p<0.001), NYHA III stadium (39% vs. 33%; p<0, 0008), ischemic etiology (56% vs. 44%; p<0.001), previous acute myocardial infartion (42, 9% vs. 36%; p<0.001), a percutan coronaria intervention (35% vs. 25%; p<0.001) compared to non-DM patients. Those patients with DM showed a 25% higher risk of all-cause mortality (HR 1.25; 95% CI 1.12-1.40; p‹0.01) then non-DM patientes, also observable after adjusting for relevant clinical covariates such as age, gender, atrial fibrillation and the addition of an ICD (HR 1.17; 95% CI 1.06-1.31; p‹0.01). Conclusions: Adding an ICD for CRT patients with diabetes reduces the risk of all-cause mortality significantly by 32% (HR 0, 68; CI 0, 56-0, 82; p‹0.001) during the first six years but diminished on longer follow-up time (HR 0, 95; CI 0, 80-1, 12; p=0, 54).